Fanatisme Suporter dan Perilaku Agresif dalam Olahraga: Tinjauan Literatur Sosiologis - Nufi Saidatus Tsaniyah; Himawan Wismanadi; Abdul Aziz Hakim; Achmad Widodo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Supporter fanaticism is a social phenomenon commonly found in the world of sports and can have both positive and negative impacts. This study aims to examine the relationship between supporter fanaticism and aggressive behavior in the context of sports through a sociological approach. The method used is a literature review by analyzing relevant scientific articles, books, and research reports. The findings indicate that supporter fanaticism often stems from a strong collective identity, which under certain conditions can lead to aggressive behavior, both verbal and physical. Factors such as extreme group identification, inter-group provocation, and socio-cultural conditions contribute to the potential for aggression. This study provides implications for supporter management in sports, particularly in creating a safe and healthy match atmosphere. A sociological approach helps to understand supporter group dynamics more holistically and serves as a foundation for formulating preventive policies against violence in sports.